Salt-washed graphene oxide and its cytotoxicity - Mrózek, Ondřej; Melounková, Lucie; Smržová, Darina; Machálková, Aneta; Vinklárek, Jaromír; Němečková, Zuzana; Komárková, Bára; Ecorchard, Petra (Journal of hazardous materials, 2020)
The carbon nanomaterials and congeners, e.g., graphene or graphene oxide (GO), dispose of numerous unique properties, which are not necessarily intrinsic but might be related to a content of impurities. The oxidation step of GO synthesis introduces a considerable amount of metallic species. Therefore, large-scale purification is an actual scientific challenge. Here we describe new purification technique (salt‑washing), which is based on three consecutive steps: (a) aggregation of GO sheets with NaCl (b) washing of the aggregates and (c) removing of the salt to afford purified GO (swGO). The considerably improved purity of swGO was demonstrated by ICP and EPR spectroscopy. The microscopic methods (TEM with SEAD, AFM) proved that the salt-washing does not affect the morphology or concentration of defects, showing the aggregation of GO with NaCl is fully reversible. The eligibility of swGO for biomedical applications was tested using fibroblastic cell cultures. The determined IC50 values clearly show a strong correlation between the purity of samples and cytotoxicity. Although the purification decreases cytotoxicity of GO, the IC50 values are still low proving that cytotoxic effect is not only impurities-related but also an intrinsic property. These findings may represent a serious limitation for usage of GO in biomedical applications.
Keywords: nanostruktury; chlorid sodný; oxidace-redukce; Oxidation-Reduction; Sodium Chloride; grafit; Nanostructures; Graphite